Rivaroxaban for Stroke Prevention after Embolic Stroke of Undetermined Source - Hart, Robert G; Sharma, Mukul; Mundl, Hardi; Kasner, Scott E; Bangdiwala, Shrikant I; Berkowitz, Scott D; Swaminathan, Balakumar; Lavados, Pablo; Wang, Yongjun; Wang, Yilong; Davalos, Antonio; Shamalov, Nikolay; et al. (The New England journal of medicine, 2018)
In a randomized trial involving patients who had a first stroke from an embolus of unknown source, rivaroxaban at a daily dose of 15 mg did not result in a lower incidence of recurrent stroke than aspirin at a dose of 100 mg. Bleeding rates were higher with rivaroxaban.